GU-CA-COVID: a clinical audit among Italian genitourinary oncologists during the first COVID-19 outbreak. (October 2021) - Bersanelli, Melissa; Buti, Sebastiano; Rizzo, Mimma; Cortellini, Alessio; Cattrini, Carlo; Massari, Francesco; Masini, Cristina; Vitale, Maria Giuseppa; Fornarini, Giuseppe; Caffo, Orazio; Atzori, Francesco; Gatti, Alice; et al.
Background: Considering the growing genitourinary (GU) cancer population undergoing systemic treatment with immune checkpoint inhibitors (ICIs) in the context of the COVID-19 pandemic, we planned a clinical audit in 24 Italian institutions treating GU malignancies. Objective: The primary objective was investigating the clinical impact of COVID-19 in GU cancer patients undergoing ICI-based therapy during the first outbreak of SARS-CoV-2 contagion in Italy. Design, setting, and participants: The included centers were 24 Oncology Departments. Two online forms were completed by the responsible Oncology Consultants, respectively, for metastatic renal cell carcinoma (mRCC) and metastatic urothelial carcinoma (mUC) patients receiving at least one administration of ICIs between 31 January 2020 and 30 June 2020. Results and limitation: In total, 287 mRCC patients and 130 mUC patients were included. The COVID-19 incidence was, respectively, 3.5%, with mortality 1%, in mRCC patients and 7.7%, with mortality 3.1%, in mUC patients. In both groups, 40% of patients developing COVID-19 permanently discontinued anticancer treatment. The pre-test SARS-CoV-2 probability in the subgroup of patients who underwent nasal/pharyngeal swab ranged from 14% in mRCC to 26% in mUC. The main limitation of the work was its nature of audit: data were not recorded at the single-patient level. Conclusion: GU cancer patients undergoing active treatment with ICIs have meaningful risk factors for developing severe events from COVID-19 and permanent discontinuation of therapy after the infection. Treatment delays due to organizational issues during the pandemic were unlikely to affect the treatment outcome in this population.